A New Steroidal Alkaloid from the Leaves of Pistacia atlantica subsp. Mutica of Iranian Origin - HADI MESHKATALSADAT, MOHAMMAD; SADEGHI SARABI, REZA; MIRALEI, MOHAMMAD (Asian Journal of Chemistry, 2010)
A new sterodial alkaloid named pistacimidelor has been isolated from the leaves of Pistacia mutica and characterized as 3β-dimethylamino-con-5-enin-18-one-19β,22β-dimethyl (1).